Clinician communication strategies associated with increased uptake of the human papillomavirus (HPV) vaccine: A systematic review. (15th August 2022) - Constable, Catherine; Ferguson, Kyle; Nicholson, Joey; Quinn, Gwendolyn P.
Abstract: Human papillomavirus (HPV) is currently linked to almost 35, 000 new cases of cancer in women and men each year in the United States. Gardasil‐9 (Merck & Company), the only HPV vaccine now available in the United States, is nearly 100% effective at preventing precancers caused by oncogenic HPV types. In the United States, however, only about one half of adolescents are up to date with HPV vaccination. It is well known that health care clinicians' recommendations play a significant role in parents' decisions regarding HPV vaccination. A growing body of literature examines specific communication strategies for promoting uptake of the HPV vaccine. A comprehensive review of the evidence for each of these strategies is needed. The authors searched the PubMed, EMBASE, Cochrane Central Register of Controlled Trials, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, and Web of Science Complete databases for original articles with a defined clinician communication strategy and an outcome of HPV vaccine uptake or intention to vaccinate (PROSPERO registry no. CRD42020107602). In total, 46 studies were included. The authors identified two main strategies with strong evidence supporting their positive impact on vaccine uptake: strong recommendation and presumptive recommendation . Determinations about a causal relationship were limited by the small numbers of randomized controlled trials. There is also opportunity for more research to determine the effects of motivational interviewing and cancer‐prevention messaging.